Subjective judging systems: A review of the dressage scoring system used at London 2012 - Heap, C.; Lewis, V. (11th International Conference International Society for Equitation Science, 2015)
Traditionally, dressage at the Olympics was judged by 5 judges positioned at E, H, C, M and B. Each Judge scored the individual movements of the test out of 10, zero if the movement was not executed and ten given if the movement was excellent. The collective marks are split into four sections comprising of paces (freedom and regularity), impulsion (desire to move forward, elastic of the steps, suppleness of the back and engagement of the hind quarters), submission (attention and confidence, harmony, lightness and ease of movement, acceptance of the bridle and lightness of the forehand) and riders position incorporating correctness and effect of the aids. Subjective judging has drawbacks including position of the judge, nationalism, home advantages, expectation bias and order effects. In an attempt to make the judging more objective the F.E.I. added two extra judges (positioned at K and F) and a separate supervisory panel to overturn judging decisions at the London 2012 Olympic Games. Data from the London Games was reviewed retrospectively with the aim to look at whether the new system of judging made an effect on the medal and individual ranking positions. Data was analysed using descriptive statistics and SPSS. A Kolmogorov- Smirnov Normaily test was used to see if the data was normally distrupued. Then an paired t-test was used to compare the means for the two groups as the raw data was continuous and dependent variable. Through analysis it was found that the new system has made no significant difference to the average marks given to individual competitors nor the team medals (GP p value 0.774 and GPS p value 0.860 respectively). Position changes within individual ranking was not seen, meaning the same competitors progressed to the individual freestyle final. Further research include analysis of the individual freestyle final, which is judged differently to the Grand Prix and Grand Prix Special. Position of the judge effecting marks, nationalism and discarding the high and low marks. Using other subjective sports to assess the different ways of judging may enable the FEI and dressage governing bodies to establish more ways to make the sport more objective. Areas for further research for potential use in dressage include video analysis, discarding high and low marks and specific judging for different areas of the test. Overall the judging field of dressage needs more research within the field to enable governing bodies to implement the most effective method of judging, allowing more objective judging decisions to be made. LP: The new dressage judging system introduced for the London 2012 Olympic Games which included two extra judges and a separate supervisory panel did not affect the overall results of the team or individual competition if it had been judged using the old system.